The Role of Electronic Word of Mouth in the Form Of Customer Reviews on Emina Products’ Online Purchase Intention at Universitas Padjadjaran's Students - Silviana, Rachmi; Sulastiana, Marina; Nugraha, Yus (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
During the COVID-19 pandemic, the purchase of beauty products experienced a significant increase, with Emina emerging as one of the brands with notably high sales. This study aims to examine and delineate the role of electronic word of mouth (eWOM), specifically consumer reviews, in influencing the online purchase intention of Emina make-up products among students at Universitas Padjadjaran. The research employed adapted instruments measuring perceptions of eWOM and online purchase intention. A total of 229 participants were selected through a convenience sampling method. Data collection was conducted via a self-administered online questionnaire distributed through Google Forms. The analysis involved descriptive statistics, multiple regression, and supplementary testing using the Kruskal-Wallis Test. Findings reveal that eWOM measured through its three dimensions: credibility, quality, and quantity collectively accounted for 20.6% of the variance in online purchase intention. Among these dimensions, eWOM credibility emerged as the most influential, contributing 53.3%, followed by quality at 25.5%, and quantity at 21.2%. Furthermore, the data indicated significant variation in purchase intentions among participants, suggesting that increased exposure to consumer reviews correlates with a higher likelihood of intending to purchase and proceeding with the purchase of Emina products.